Confirmation Study Of Vipera Palaestinae (Werner, 1938) (Reptilia: Viperidae) Presence In The Syrian Coastal Region (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
A field survey was done to study the distribution of Vipera palaestinae (Werner, 1938) in the Syrian coastal region ,through specimens collection and conducting a taxonomic study.     As a result,Vipera palaestinae was recorded in the southwestern area of the Syrian coastal region, with the possibility of presence in other areas of the region, due to the existence of the suitable environment conditions required for its distribution. تمت دراسة تحديد توزع أفعى فلسطين Vipera palaestinae (Werner, 1938)، في المنطقة الساحلية السورية، حيث جمعت العينات وتم اجراء الدراسة التصنيفية لها. وقد أظهرت النتائج تواجد النوع Vipera palaestinae في المنطقة الجنوبية الغربية من الساحل السوري، مع احتمالات تواجدها في المناطق المختلفة من المنطقة الساحلية وذلك بسبب وجود البيئة الملائمة لانتشارها.